If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -47 = 107 Reorder the terms: -47 + 11x = 107 Solving -47 + 11x = 107 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '47' to each side of the equation. -47 + 47 + 11x = 107 + 47 Combine like terms: -47 + 47 = 0 0 + 11x = 107 + 47 11x = 107 + 47 Combine like terms: 107 + 47 = 154 11x = 154 Divide each side by '11'. x = 14 Simplifying x = 14
| xy-5y^2=-5 | | 7x+5(-3x+4)=20 | | .3x+.2y-80=0 | | -2m=-8 | | x+0.05x=36225 | | -18=x/13 | | Y=0.66X+3.8 | | 93m=4m+14 | | 3S+8=4S+4 | | -2(8)+8y=6 | | 4.7t+13=-5.33 | | 49-3m=m+14 | | .3x+.2y=80 | | -12x-12=6 | | 9+7x=-75 | | X=0.46 | | -14/13=m/13 | | -6m-12=6 | | 4.7-3y=-10.9 | | 13=p/2 | | 18=a/20 | | 13-6y=-29 | | B/19=12/19 | | x^3-2x^2=36x+72 | | -160=10k | | 7+6t=-35 | | -2=7k/-4 | | 1r-4+6r=8+-4 | | -15+3x=15 | | 8E-18=10E+30 | | 5q-17=13 | | 4x+9=6-y |